Public Organizations in the Development of Informatization of Education: A Case Study from Russia - Sofronova, Nataliya V.; Romanenko, Yuriy A.; Belchusov, Anatoly A.; Ignatieva, Emilia A. (Journal of History Culture and Art Research, 2019)
The paper addresses the identified gap existing in the contemporary scholarship by providing a case study of a public organization’s involvement in addressing pressing issues in the field of informatization of education. First of all, on the basis of the literature review conducted by us, we identify a total of three key areas of informatization of education: (1) intensive development of digital information technology in education; (2) scientific understanding and forecasting of informatization of education; (3) introduction of achievements made in science and technology into the practice of the educational process. Within the case, we briefly outline the key steps in the development of informatization of education in the Soviet Union and the Russian Federation. Then we gradually review the key activities conducted by the Academy of Informatization of Education in different regions, additionally focusing on its leading regional branch. A detailed review allows us to develop a clear understanding of the main direction of informatization of education in Russia, as well as the role played by a public organization in these processes. Also, we emphasize the role of entrepreneurial activities of public organizations to sustain themselves, as well as the need to apply for grant support. Within the three key directions of informatization of education outlined above on the basis of the literature review conducted by us, we also review social projects conducted by public organizations in Russia, particularly those which received financial support from the largest Russian Presidential Grants Fund. Such an analysis allows us (a) to trace federal priorities in providing financial support for public organizations working in the field of informatization of education, as well as (b) to analyze a regional dispersion of the projects supported, including their variety and scope. The research conducted clearly shows that public organizations mainly cover only two key directions, but they almost completely ignore the third demanding direction – “scientific understanding and forecasting of processes in informatization of education.”